Memorandum of understanding between Universiti Teknologi MARA and Superdough / Fakulti Filem, Teater dan Animasi - Universiti Teknologi MARA, Fakulti Filem, Teater dan Animasi
Memorandum of understanding on friendship and cooperation for friendship, cooperation and collaboration.